2008
DOI: 10.1007/s10964-008-9366-8
|View full text |Cite
|
Sign up to set email alerts
|

Family Transitions and Later Delinquency and Drug Use

Abstract: Changes in the family structure can be very disruptive to adolescents who live in those families. This article examines the impact of the number of family transitions on delinquent and drug-using behavior. Specifically, the effect of family transitions is hypothesized to be mediated by problems within the family, school, and peer settings. A sample of 646 boys (73%) and girls (27%) taken from a longitudinal panel study of high-risk adolescents are used to examine these hypotheses. For girls, little support is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 40 publications
3
17
0
4
Order By: Relevance
“…Family transitions predicted membership in both the negligible and early starter/declining group as compared to the late starters. Krohn et al (2009) found similar results in terms of this gender difference in the effect of family transitions on delinquency. Additionally, there was one significant effect for living in a single parent household-an increased risk of being in the chronic group as compared to the late starter (essentially predicting a lower level of delinquency at age 10).…”
Section: Discussionsupporting
confidence: 72%
“…Family transitions predicted membership in both the negligible and early starter/declining group as compared to the late starters. Krohn et al (2009) found similar results in terms of this gender difference in the effect of family transitions on delinquency. Additionally, there was one significant effect for living in a single parent household-an increased risk of being in the chronic group as compared to the late starter (essentially predicting a lower level of delinquency at age 10).…”
Section: Discussionsupporting
confidence: 72%
“…We concluded that group differences in the effect of instability on the risk behaviors considered can be attributed to variation in the levels of social protection and socioeconomic stress experienced, rather than to group differences in how they are experienced. Recent work (Cavanagh & Huston, 2008; Cooper, Osborne, Beck, & McLanahan, 2008; Krohn et al, 2009) suggests that the direct association between family structure change and behavioral adjustment is stronger for boys than for girls. In models split by gender, we found a similar magnitude and significance of family instability effects for boys and girls, with one exception: the effect of instability in predicting sexual initiation for Black boys was significantly weaker than the effect for White boys in the baseline model (consistent with the pooled model presented in table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Although a full causal chain has not been identified, various explanations for why instability matters for children’s behavior have been supported by empirical research. These include children’s repeated exposure to poor union quality in the context of dissolving or newly forming unions (Fomby & Osborne, 2008), compromised parent-child relationships in response to persistent instability (Cavanagh, 2008), maternal stress following a family structure transition (Osborne & McLanahan, 2007), and co-occurring disruption to broader social contexts (Krohn, Hall & Lizotte, 2009). …”
mentioning
confidence: 99%
“…Most, but certainly not all (e.g., Amato, 2001; Cavanagh, 2008; Fomby & Cherlin, 2007; Krohn, Hall, & Lizotte, 2009; Magnuson & Berger, 2009; Waldfogel, Craigie, & Brooks-Gunn, 2010), of the research focuses on divorced families and highlights that union dissolution places children, particularly adolescents (Amato, 2001; Cavanagh, 2008), at elevated risk for ensuing maladjustment. From his meta-analysis of marital divorce studies, Amato concluded that children who experience parental divorce “score significantly lower on measures of academic achievement, conduct, psychological adjustment, self-concept, and social relations” (p. 355).…”
Section: Family Transitionsmentioning
confidence: 99%